Optic Pathway Gliomas in Neurofibromatosis Type 1: An Update: Surveillance, Treatment Indications, and Biomarkers of Vision - de Blank, Peter M. K. (J Neuroophthalmol, 2017)
Optic pathway gliomas (OPGs) occur in 15%–20% of children with neurofibromatosis type 1 (NF1), leading to visual deficits in fewer than half of these individuals. The goal of chemotherapy is to preserve vision, but vision loss in NF1-associated OPG can be unpredictable. Determining which child would benefit from chemotherapy and, equally important, which child is better observed without treatment can be difficult. Unfortunately, despite frequent imaging and ophthalmologic evaluations, some children experience progressive vision loss before treatment. Indications for chemotherapy usually are based on a comprehensive, quantitative assessment of vision, but reliable vision evaluation can be challenging in young children with NF1-OPG. The ability to identify and predict impending vision loss could potentially improve management decisions and visual outcomes. To address this challenge, ophthalmologic, electrophysiologic, and imaging biomarkers of vision in NF1-OPG have been proposed. We review current recommendations for the surveillance of children at risk for NF1-OPG, outline guidelines for initiating therapy, and describe the utility of proposed biomarkers for vision.